Planetary boundaries as a way of assessing environmental performance: a methodological approach proposal - Leite, Patricia Fernanda Dionizio; Hourneaux Junior, Flavio (Revista de Administração da UFSM, 2024)
Objective: This study aims to demonstrate how planetary boundaries can serve as a method for evaluating the environmental performance of organizations. Methodology: The study is based on different methods of data collection and analyses, based on the literature on planetary boundaries and their measurement, secondary data collection and the use of two illustrative examples with two companies operating in the oil and gas sector in the upstream segment. Results: It was initially necessary to validate the downscaling of planetary boundaries to the business analysis level to apply the proposed conceptual model to two cases of companies operating in the oil and gas sector in the upstream segment. The proposed downscaling method proved to be adequate, effective, and plausible, as did the use of planetary boundaries as a method for evaluating the environmental performance of organizations. Implications: This study established contributions of methodological and practical natures, which allows companies in the sector to evaluate and be evaluated based on the need to respect the biophysical limits of the Earth system. Originality/Relevance: The concept of planetary boundaries provides a starting point for understanding the compatibility between the search for sustainable development and the current economic model, since the natural capital consumed is physically finite. In addition, a critical factor in this search is the role played by companies since the increased pressure on the consumption of natural resources directly impacts business operations.